Evaluation of Pregabalin Therapy in Peripheral Neuropathy - Shimizu, Kazutaka; Taniyama, Yoshiaki; Azuma, Junya; Sanada, Fumihiro; Iwabayashi, Masaaki; Yamane, Yuki; Yamasaki, Hiroko; Akasaki, Atsuko; Morishita, Ryuichi (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2013)
The mechanism of peripheral neuropathy has not been sufficiently clarified, and medical therapy for peripheral neuropathy is not established. Only a few reports have evaluated the analgesic effects of pregabalin in different diseases. In the present study, the effects of pregabalin in both orthopedic patients and surgical patients were compared, and the improvement of peripheral neuropathy was quantified. A questionnaire-based study was performed on numbness and the intensity of pain in orthopedic patients with organic diseases like spinal canal stenosis and in surgical patients with neuropathy from anti-cancer treatment. The data for patients who were prescribed pregabalin were examined using a numerical rating scale (NRS). Improvement of symptoms was observed in categories such as numbness, pain with numbness, and pain without numbness in orthopedic patients. NRS value decreased by 33% in all patients who were prescribed pregabalin. Drowsiness, a side effect of pregabalin, mostly disappeared over 4 weeks after pregabalin administration. Further, when combining drugs with pregabalin, the frequency of numbness and pain with numbness tended to be decreased by two agents (pregabalin + NSAID), and was significantly decreased by three agents (pregabalin + NSAID + muscle relaxant), as compared with pregabalin-only treatment. The present study revealed the analgesic effect of pregabalin with regards to pain both with and without numbness. The data suggest that pregabalin is effective especially in orthopedic patients with organic injury of nerves.
Keywords: numbness